2014
DOI: 10.1002/mrm.25128
|View full text |Cite
|
Sign up to set email alerts
|

Gadofosveset‐based biomarker of tissue albumin concentration: Technical validation in vitro and feasibility in vivo

Abstract: PurposeThere is currently no adequate method of mapping physiologic and pathophysiologic tissue albumin concentrations in human subjects. The objective of this study was to devise and evaluate a biomarker of regional albumin concentration using gadofosveset-enhanced MRI.Theory and MethodsA binding and relaxation model was devised and evaluated in vitro in solutions of albumin at 3.0 Tesla (T) and 4.7T. The method was evaluated in the heart in seven volunteers at 3.0T.ResultsMRI-derived estimates of albumin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Gadofosveset binds reversibly to serum albumin, increasing its molecular weight from 0.9 to 67 kDa. Under physiological conditions, albumin has a low transcapillary exchange rate into the interstitial compartment, estimated to be on the order of 5% per hour, which explains the propensity of gadofosveset to remain within blood vessels ( Richardson et al, 2015 ). In both species, gadofosveset did not reveal dural lymphatics, especially on T1-black blood images ( Figure 2 and Figure 2—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gadofosveset binds reversibly to serum albumin, increasing its molecular weight from 0.9 to 67 kDa. Under physiological conditions, albumin has a low transcapillary exchange rate into the interstitial compartment, estimated to be on the order of 5% per hour, which explains the propensity of gadofosveset to remain within blood vessels ( Richardson et al, 2015 ). In both species, gadofosveset did not reveal dural lymphatics, especially on T1-black blood images ( Figure 2 and Figure 2—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, considering that elimination half-lives in humans are six to nine fold longer than in mice, these results indicated that the one order of magnitude higher affinity constant to HSA for Gd-AAZTA-MADEC may allow robust steady-state MRI angiographic acquisitions [40]. Beyond angiography, recent studies have utilized MS-325 as a biomarker for tissue albumin concentration for assessing reperfused myocardial infarction [41]. The design of a new blood pool agent with optimized albumin binding properties may allow further improvements of this new clinical indication.…”
Section: Discussionmentioning
confidence: 99%
“…48 Prior to in vivo reported. 49,50 The analysis of the myocardial uptake curve with the 2CX model resulted in good agreement of MBF estimation, with some trends towards higher MBF values and lower variability for Vasovist. Similar observations were noted by Jerosch-Herold et al, 51 who suggested that the use of an intravascular (instead of an extracellular) contrast agent allows for a reduction of the degrees of freedom for modeling tissue uptake (with a compartment BTEX model) and hence results in improved accuracy of MBF estimation.…”
Section: Discussionmentioning
confidence: 79%
“…Because of its long circulation time, it was primarily designated for contrast‐enhanced angiography, but it has also been studied for cardiac applications, including perfusion estimation . Prior to in vivo application in the current study, the relaxivity of Vasovist was measured in a solution of saline and bovine serum albumin, yielding a relaxivity constant of ≈ 5mM −1 s −1 , which is significantly higher than that measured for Gadovist (≈ 4mM −1 s −1 ) and in line with values previously reported . The analysis of the myocardial uptake curve with the 2CX model resulted in good agreement of MBF estimation, with some trends towards higher MBF values and lower variability for Vasovist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation